UPAYA MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING BAGI SANTRI KELAS 2 IBTIDA’IYAH PONDOK PESANTREN DARUL MUTTAQIEN BOLONG SELOPAMPANG TEMANGGUNG (STUDY MODEL PEMBELAJARAN KITAB AL JURUMIAH) - Dila Laila Muthoharoh; Ngarifin Shidiq; Mukromin Mukromin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Education is a vital aspect of human life that cannot be separated. Education functions as a process designed to achieve certain goals and improve human quality. One way to advance the quality of education is by improving the quality of learning, where the main role is held by teachers. This article aims to analyze efforts to improve the ability to read the Yellow Book for students of class 2 Ibtida’iyah Darul Muttaqien Bolong Selopampang Temanggung Islamic Boarding School (Study of the Al Jurumiah Book Learning Model). This study uses a descriptive qualitative method with a field study approach. The research subjects include caregivers, ustadz teaching the Al-Jurumiyah book, and students of class 2 Ibtida’iyah Darul Muttaqien Islamic Boarding School. Data collection was carried out through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that Al-Jurumiyah learning is effective in improving the ability to read the yellow book of students. Supporting factors include the ustadz’s varied teaching methods and students’ learning motivation, while inhibiting factors include limited time, differences in student abilities, and lack of supporting learning resources. Therefore, learning Al-Jurumiyah can be an effective strategy for improving the reading skills of students at the Darul Muttaqien Islamic Boarding School.